2009
DOI: 10.1088/0031-9120/45/1/012
|View full text |Cite
|
Sign up to set email alerts
|

Thai high-school students’ misconceptions about and models of light refraction through a planar surface

Abstract: This article investigates the optics misconceptions of 220 year 11 Thai high-school students. These misconceptions became apparent when the students attempted to explain how an object submerged in a water tank is 'seen' by an observer looking into the tank from above and at an angle. The two diagnostic questions used in the study probe the students' ability to use a ray diagram to explain the relationship between object, image and observer, and then to use the ray diagram to qualitatively determine the positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
29
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 40 publications
6
29
0
1
Order By: Relevance
“…When the literature is reviewed, it is seen that students from each level have inadequate and incomplete knowledge and misconceptions related to the light and sound topics [28,32,35,36,37,38,40,41]. It is also seen that the teachers and pre-service teachers, who will educate those students, have deficient and inadequate knowledge and even misconceptions about this topic.…”
mentioning
confidence: 99%
“…When the literature is reviewed, it is seen that students from each level have inadequate and incomplete knowledge and misconceptions related to the light and sound topics [28,32,35,36,37,38,40,41]. It is also seen that the teachers and pre-service teachers, who will educate those students, have deficient and inadequate knowledge and even misconceptions about this topic.…”
mentioning
confidence: 99%
“…Some studies reported learners" alternative ideas on light and vision (Rice & Feher 1987;Selley 1996) while others dealt with shadows (Chen 2009). Evidence of research done on learners" ideas about refraction was also found (Kaewkhong et al 2008(Kaewkhong et al , 2010Sengoren 2010).…”
Section: Introductionmentioning
confidence: 86%
“…Many studies have explained children's alternative conceptions about light, vision and optical phenomena. These suggest that the alternative knowledge held by learners with regard to the optics phenomena may be different from formal scientific knowledge (Saxena 1991;Osborne et al 1993; Kaewkhong, Mazzolini, Emarat & Arayathanitkul 2010).…”
Section: Introductionmentioning
confidence: 94%